Pandemic Politics within a System of Entangled Political Economy - Marta Podemska-Mikluch; Richard E. Wagner (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
This essay uses entangled political economy to explore how concerns over Covid-19 have influenced conduct within the public square. Entangled political economy represents a merging of ideas that Frank Knight (1933) and Harold Lasswell (1936) set forth to indicate that politics and economics dealt with the same societal material. We explore the relationship between entanglement and public reason within a context of Michael Polanyi's (1962) conceptualization of a Republic of Science. The point of our paper is not to offer some critique of particular policy measures but to advance our understanding of how democratic societies operate in stressful times. It seems patently clear that Covid-19 presents some difficult problems of public health regarding a sometimes-lethal contagious disease that spreads through personal interaction. Times of crisis like that which many people think Covid-19 presents surely amplifies the challenges that policy formation presents to democratic societies. Our interest in this paper, however, lies not in selecting among different policies that people have proposed to combat the pandemic. Rather, we explore the properties of different organizational arrangements through which contestation among political, economic, and scientific entities influence the emergence of societal outcomes. To do this, we adopt the approach of entangled political economy which Wagner (2016) summarizes. Entangled political economy contrasts with the standard notion of additive political economy. With additive political economy, political action is independent of economic action as is entailed in the presumption that political action offsets market failures. In contrast, with entangled political activity there is continual interaction between political and economic entities, sometimes to mutual advantage and sometimes not, but politics and economics do not represent distinct realms of activity in any case. At the core of our analysis lies recognition of the wisdom of Frank Knight's oft-made remark that our most severe problem with knowledge does not lie in what we don't know but rather lies in what we know that isn't true. There might well be one best response to Covid-19, but there is no universal agreement about what that response might be. Many people claim to know what's best, and not all of them can be right. In the face of such systemic ignorance, there is no effective option to relying on processes of social contestation to winnow down the possibilities. Hence, we focus on contestation within a policy-making processes that entails interaction among political, economic, and scientific entities. That contestation, moreover, cuts across different linguistic communities. The scientific community mostly uses languages grounded in concepts and categories of such fields as molecular biology, epidemiology, virology, and statistics. The commercial or economic community mostly works with languages grounded in revenue, costs, and profits. The political community mostly works with languages grounded in public perception and the reduction of technical categories and concepts to those that seem intuitively reasonable or plausible. The social process of contestation thus resembles a three-ring circus where activity in the main political ring is shaped by activities undertaken within the commercial and scientific rings, and with that shaping running in both directions. We examine the societal impact of Covid-19 from the perspective of entangled political economy which construes societies as dense and complex ecologies of interacting enterprises. The framework of entangled political economy is built on recognition of the dispersed nature of knowledge. Within this analytical framework, policy is not so much an object of choice by some ruling coalition as it is an emergent outcome of interaction among interested participants as shaped through an organizationally structured process of political competition (Podemska-Mikluch 2014). The framework of entangled political economy recalls the formulations by two scholarly giants associated with the University of Chicago in the 1930~s, Frank H. Knight (1933) and Harold D. Lasswell (1936), each of whom articulated nearly congruent visions of the domains of economics and politics, and with nearly a century later this vision now carrying the label entangled political economy. In The Economic Organization, Knight (1933) explained that any society will have to address the same set of questions: what will be produced, how it will be produced, and how much of that output different people will receive. In very small societies, these decisions might be made explicitly through some procedure of collective choice. In large societies, such explicit choice is impossible. Nonetheless, those three sets of decisions will be necessary in even the largest of societies. Knight's point was simply that the making of such decisions was present in the very operation of the society, even though there might be innumerable processes for reaching such decisions. For Lasswell (1936), politics addressed questions of who gets what, when they get it, and how they get it. It's plain to see that what Wagner (2016) describes as entangled political economy is congruent with Knight's and Lasswell's formulations of the problems that are common to all societies. Furthermore, entangled political economy suggests that both market and political entities are similar in being led by leaders who seek to be successful at what they do. One significant difference between political and market enterprises is that there exists a market for ownership shares in market enterprises which means that those enterprises will command market value. This contrast between the two categories of enterprise influences the types of interaction that occur between those enterprises. All the same, what we denote as policy outcomes emerge through processes of contestation across the three rings. How the outcomes of that contestation might measure up against some imagined standard of societal welfare is something about which many people might have opinion, only there is no god-like vantage point like Mount Olympus from which correct or true judgment might be rendered. We open the paper with an overview of the role the concept of public goods and public reason has played in advancing lines of demarcation between political and commercial activity. We then contrast this effort at demarcation with the efforts of Elinor Ostrom (1990) and her associates to explain how people often are able to overcome the public goods problems they face without resorting to some arbitrary imposition of power to resolve theoretical impasses. Following this, we contrast the assembly of knowledge within an idealized setting of a Republic of Science (Polanyi 1951; 1962) with recognition that science and politics are inescapably entangled in settings like that which Covid-19 presents. We close by reflecting on how ideas from entangled political economy might alter the contributions social sciences might make to political processes.
Keywords: P16; D23; D78; H12; I18; 330; Epistemic Institutions; Public Policy; Covid-19; Uncertainty; Entangled Political Economy; Public Reason